Living Quran: Konstruksi Metode Tahfidz Al-Quran Di Majelis Qiraah Wat Tahfidz Pondok Pesantren Murattil Al-Quran Lirboyo Kota Kediri - Eko Zulfikar (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2019)
The maintenance of the Qur’an from the past until now gives an indication that Muslims are obliged to always maintain and keep it, by reading, writing or memorizing. It aims to keep the Qur’an on its authenticity throughout the lifetime of change and replacement. This paper will discuss the method of tahfidz al-Qur’an in the Majelis Qira’ah wat Tahfidz (MQT) pondok pesantren Murattil al-Qur’an (PPMQ) in Lirboyo, Kediri. This research was conducted with a qualitative approach. The data collection was through interviews, observation and documentation techniques. The results concluded that the MQT Assembly used various methods in the activities of tahfidz al-Qur’an, which was to read and memorize verses of the Qur’an collectively (jama’), read carefully one by one the verses of the Qur’an that would be memorized by looking at the Qur’an repeatedly (wahdah and bi al-nadzar), depositing a new memorization to ustadz or kiyai (talaqqi), memorizing back verses of the Qur’an that had been deposited to ustadz or kiyai (takrir), and playing rote to the other santri (tasmi’).